Pictonorchestia, a new genus of riparian-hopper from New Zealand (Crustacea, Amphipoda, Senticaudata, Talitridae) - Lowry, James K.; Springthorpe, Roger (Zootaxa, 2021)
Pictonorchestia, a new genus of talitrid amphipod is established for Orchestia dentata Filhol, 1885, from New Zealand. It is characterised by the dactylus of gnathopod 2 which has a well-developed projection on the posterior margin which interlocks with a shallow sinus on the palm and a proximal spine which defines the palm. It differs from other talitrid genera in having gnathopod 1 carpus and propodus with palmate lobes, gnathopod 2 dactylus not modified distally, pleopods all well-developed, uropod 1 exopod with marginal setae in one row. Pictonorchestia is also unusual in having an incrassate antenna 2, but pereopod 7 not sexually dimorphic, a combination shared by only ten other genera, none of which have the gnathopod 2 dactylus with a prominent projection on the posterior margin.